Street Politics of Mourning. Narrating Loss in Housing Protests with and beyond Hannah Arendt - Bstieler, Michaela (HannahArendt.net, 2024)
In this article, I explore the relation between mourning and protest, body and streetpolitics, with Hannah Arendt and SaidiyaHartman. I argue that deeply felt pain requires aform of aesthetic translation in order to be effective as a means of protest. To the extent thatdramatic singing can be understood as a figure of speech and storytelling, as Stanley Cavellsuggests, operacan narrativize even the most profound and deeply hidden grief, and can thusaddress losses that are otherwise given little or no consideration. This is the case, for example,when it comes to homelessness and displacement through processes of gentrification andprivatization. Using the Berlin protest opera Who Owns Lauratibor? (2020) as an example, Iwill show that the narration of stories, magic, and fiction through opera can not only beworld-building, but also reveal the suffering associated with the loss of one’s home.